2012
DOI: 10.1029/2012ja017832
|View full text |Cite
|
Sign up to set email alerts
|

The impact of helium on thermosphere mass density response to geomagnetic activity during the recent solar minimum

Abstract: High‐resolution mass density observations inferred from accelerometer measurements on the CHAMP and GRACE satellites are employed to investigate the thermosphere mass density response with latitude and altitude to geomagnetic activity during the recent solar minimum. Coplanar orbital periods in February 2007 and December 2008 revealed the altitude and latitude response in thermosphere mass density for their respective winter hemispheres was influenced by the relative amount of helium and oxygen present. The CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 29 publications
3
62
0
Order By: Relevance
“…The existence of the thermosphere winter helium bulge was later confirmed by directly measuring helium concentrations using satellite-borne mass spectrometers [e.g., Reber et al, 1968;Mauersberger et al, 1976]. The winter helium bulge has been used to explain anomalous behavior in thermospheric mass density [e.g., Keating and Prior, 1968;Thayer et al, 2012;Liu et al, 2014] and as an indicator of thermosphere dynamics [Reber, 1976].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of the thermosphere winter helium bulge was later confirmed by directly measuring helium concentrations using satellite-borne mass spectrometers [e.g., Reber et al, 1968;Mauersberger et al, 1976]. The winter helium bulge has been used to explain anomalous behavior in thermospheric mass density [e.g., Keating and Prior, 1968;Thayer et al, 2012;Liu et al, 2014] and as an indicator of thermosphere dynamics [Reber, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…New estimates of helium from satellite accelerometer data during this past extreme solar minimum [Liu et al, 2014] and helium's impact on thermosphere mass density [Thayer et al, 2012] reveal the importance of properly describing the dynamic change of helium to characterize the mass density state of the upper atmosphere. But the mechanisms responsible for the helium distribution have not been adequately described nor has helium been implemented in modern general circulation models to enable a more complete evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…These data sets now comprise the majority of our understanding of thermospheric composition, the empirical basis of which is embodied by the Mass Spectrometer and Incoherent Scatter (MSIS) series of models [13,14,48], successors of the Ogo 6 model. More recently, Thayer et al [74] inferred strong signatures of helium from differences in total mass densities measured at two different altitudes by high-precision accelerometers on board the Challenging Mini-Satellite Payload (CHAMP) and Gravity Recovery and Climate Experiment (GRACE) satellites [70]. Liu et al [34] extended this work, showing that the response of the mass density vertical profile during a geomagnetic disturbance is quite sensitive to the atomic oxygen/helium transition height.…”
Section: Introductionmentioning
confidence: 69%
“…This choice was made as a compromise between including as much data as possible and eliminating measurements in which the CHAMP altitude was too low compared to the target height of 450 km. Besides, studies showed that the MSISE-00 model was not accurate during the extreme solar minimum of 2008-2009 owing to an unexpectedly large amount of helium [Thayer et al, 2012;Liu et al, 2014a], which would affect our height corrections based on MSISE-00.…”
Section: Data and Model Constructionmentioning
confidence: 99%
“…Thus, although we do not have composition data for the present study, the change in the composition is expected to add complexity to the thermospheric response to solar wind forcing described in the following section. (See also Thayer et al [2012] for the composition effect on the total mass density at CHAMP and GRACE altitudes. )…”
Section: Quiet Modelmentioning
confidence: 99%